An evaluation of the library ambience of the University of the Philippines College of Education library based on user perception - Olid, Jerwin Joshua R (2015)
Library ambience is significant for the efficiency in meeting the needs of the patrons and is critical in the process of planning and maintaining right atmospheric factors. This study is focused on evaluating the library ambience of the UP College of Education library by the response of its patrons.